Personal Health, Person-centred Health and Personalised Medicine – Concepts, Consumers, Confusion and Challenges in the Informatics World - Rigby, M. (Yearbook of Medical Informatics, 2012)
To define and assess ‘Consumer Health Informatics’ and related emergent issues in an era of new media and of personalisation of care, and from this to define what actions need to be taken to optimise benefits and address risks.Definition of key concepts; review of health personalisation, emergent health information and communication technologies and knowledge sources available to citizens and social media; and identification of unresolved issues threatening optimal use of each.A structured review supported by citations and examples.Several new aspects of consumer health informatics are emerging, including new knowledge sources, feedback on treatments and care providers, on-line videos, and a new generation of patient experience sites including those which are for profit and seek to influence treatment paradigms. Not just the information usage, but also the potential social challenges and malicious abuses, are global issues, and also transcend the traditional health community and thus should be addressed in partnership with other global agencies.
Keywords: Consumer health informatics; personal health; personalised medicine; Internet; social media; safety